Exploring the experiences, perceptions and reflections of popular electronic musicians at UK higher education institutions. Issue 2 (1st July 2015) - Thompson, Paul; Stevenson, Alex
Although formal educational institutions in the UK, and particularly in Higher Education (HE), have begun to include aspects of dance music and hip-hop styles of music in their curricula, there is still a notable lack of research into the relationship between popular electronic music-making practices, such as performance, and formal education. This study explores some of the experiences, perceptions and reflections of popular electronic musicians in formal educational institutions in the UK with a specific focus on the performance of popular electronic music. Our findings show that formal education has had some impact on the development of popular electronic musicians' practice and, in some cases, acted as an introduction to popular electronic styles of music. However, the study's findings also highlight the need to develop more comprehensive musical curricula that include popular electronic styles of music as well as the more established popular musical styles such as rock.